2020
DOI: 10.1101/2020.08.18.20166835
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

SARS-CoV-2 Infections Among Children in the Biospecimens from Respiratory Virus-Exposed Kids (BRAVE Kids) Study

Abstract: BACKGROUND: Children with SARS-CoV-2 infection typically have mild symptoms that do not require medical attention, leaving a gap in our understanding of the spectrum of illnesses that the virus causes in children. METHODS: We conducted a prospective cohort study of children and adolescents (<21 years of age) with a SARS-CoV-2-infected close contact. We collected nasopharyngeal or nasal swabs at enrollment and tested for SARS-CoV-2 using a real-time PCR assay. RESULTS: Of 382 children, 293 (77%) were SARS… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
40
2
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(53 citation statements)
references
References 40 publications
10
40
2
1
Order By: Relevance
“…Given that asymptomatic patients with a recent known COVID-19 contact were more likely to have higher viral loads in our study, one hypothesis is that the lower median viral loads in the preprocedure/preadmission testing groups reflect that more of those children had remote infection. This suggestion is supported by a recent study of children who were all close contacts of people with SARS-CoV-2 infection; that study found similar viral loads on NP swabs from children with and without symptoms (though all reported viral loads were relatively low) ( 35 ). Unfortunately, there are minimal published data describing results of testing asymptomatic populations with a wider range of potential exposure times.…”
Section: Discussionmentioning
confidence: 60%
“…Given that asymptomatic patients with a recent known COVID-19 contact were more likely to have higher viral loads in our study, one hypothesis is that the lower median viral loads in the preprocedure/preadmission testing groups reflect that more of those children had remote infection. This suggestion is supported by a recent study of children who were all close contacts of people with SARS-CoV-2 infection; that study found similar viral loads on NP swabs from children with and without symptoms (though all reported viral loads were relatively low) ( 35 ). Unfortunately, there are minimal published data describing results of testing asymptomatic populations with a wider range of potential exposure times.…”
Section: Discussionmentioning
confidence: 60%
“…Other studies have suggested that only around 20% 31 -50% 6 of population samples of CYP have symptoms. Findings from the small number of available community samples suggest that lower proportions present with fever (30% 6 32 -40% 33 ) and cough (10% 6 -35% 32 33 ), consistent with a higher proportion who are asymptomatic.…”
Section: Original Researchmentioning
confidence: 91%
“…Of great importance in the management of the pandemic is the observation that many infected individuals are asymptomatic, ranging from 20-80% 1,2,3 . Asymptomatic patients, while having faster viral clearance [4][5][6][7] , appear to have similar viral loads compared to symptomatic patients 4,5,[8][9][10][11] and, therefore, can effectively transmit the disease. Since viral load is not a reliable predictor of disease severity, we examined the genomic biology of SARS-CoV2 infection in primary patient samples for other correlates of clinical severity.…”
Section: Introductionmentioning
confidence: 99%